Game profile-based training in soccer: A new field approach - Dello Lacono, A.; Martone, D.; Cular, D.; Milic, M.; Padulo, J. (The Journal of Strength and Conditioning Research, 2017)
The aim of the study was to profile and compare the time-motion, physiological, and neuromuscular responses of both National Youth League (NYL) and UEFA Youth League (UYL) matches with those of an experimental game profile-based training (GPBT) protocol. Time-motion traits and physiological, perceptual, and neuromuscular responses were investigated in 24 male soccer players across 14 matches and 6 GPBT training sessions, for a total of 420 samples. The GPBT had a greater influence on time-motion traits and perceptual responses than the NYL and UYL matches (all p < 0.001). No significant GPBT vs. match differences were found for mean heart rate or blood lactate (F = 1.228, p = 0.304, and F = 0.978, p = 0.385, respectively). Finally, the GPBT protocol led to greater impairment of the neuromuscular explosive performances when compared with those of the postmatch scores (squat jump: F = 19.991, p < 0.001; countermovement jump: F = 61.703, p < 0.001). Results identified the GPBT protocol as characterized by relatively greater high-intensity workloads than official NYL and UYL matches, requiring increased demanding efforts. In light of these outcomes, the GPBT protocol can be considered an advantageous training method for elite soccer players, capable of stimulating the physical effort and physiological capabilities required during a match. This approach is favorable when designing a training intervention according to the principle of sport specificity, as it is based on the specific metabolic demands.